Ultrasound multiple scattering with microbubbles can differentiate between tumor and healthy tissue in vivo. (31st May 2019) - Mohanty, Kaustav; Papadopoulou, Virginie; Newsome, Isabel G; Shelton, Sarah; Dayton, Paul A; Muller, Marie
Abstract: Most solid tumors are characterized by highly dense, isotropic vessel networks. Characterization of such features has shown promise for early cancer diagnosis. Ultrasound diffusion has been used to characterize the micro-architecture of complex media, such as bone and the lungs. In this work, we examine a non-invasive diffusion-based ultrasound technique to assess neo-vascularization. Because the diffusion constant reflects the density of scatterers in heterogeneous media, we hypothesize that by injecting microbubbles into the vasculature, ultrasound diffusivity can reflect vascular density (VD), thus differentiating the microvascular patterns between tumors and healthy tissue. The diffusion constant and its anisotropy are shown to be significantly different between fibrosarcoma tumors ( n   =  16) and control tissue ( n   =  18) in a rat animal model in vivo . The diffusion constant values for control and tumor were found to be 1.38  ±  0.51 mm 2 µ s −1 and 0.65  ±  0.27 mm 2 µ s −1, respectively. These results are corroborated with VD from acoustic angiography (AA) data, confirming increased vessel density in tumors compared to controls. The diffusion constant offers a promising way to quantitatively assess vascular networks when combined with contrast agents, which may allow early tumor detection and characterization.